Gender-specific psychosocial stressors influencing mental health among women elite and semielite athletes: a narrative review. Issue 23 (11th October 2022) - Pascoe, Michaela; Pankowiak, Aurélie; Woessner, Mary; Brockett, Camilla L; Hanlon, Clare; Spaaij, Ramón; Robertson, Sam; McLachlan, Fiona; Parker, Alexandra
Abstract : Elite and semielite athletes commonly experience mental health concerns and disorders. Compared with men athletes, women athletes are at greater risk of a range of psychological stressors that contribute to health concerns and mental health disorders, which can impact their career satisfaction and longevity. In order to address and improve the mental health of women athletes, it is necessary to simultaneously tackle the gender specific psychosocial stressors that contribute to mental health outcomes. This narrative review examines the gender-specific stressors that affect mental health and well-being in women athletes, some of which are modifiable. Psychosocial stressors identified include exposure to violence, be it psychological, physical or sexual in nature, which can result in a myriad of acute and long-lasting symptoms; and inequities as reflected in pay disparities, under-representation in the media, fewer opportunities in leadership positions and implications associated with family planning and motherhood. Strategies to promote mental health in women athletes should be considered, and where possible, should proactively address gender-specific stressors likely to influence mental health in order to maximise positive outcomes in women athletes.